Perspective Contradiction Regarding Competition and Financial Stability in the Banking Sector: Review of Literature - Safitri, Ni Wayan Noviana; Wiksuana, I Gusti Bagus; Sedana, Ida Bagus Panji; Baskara, I Gde Kajeng (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
This study aims to provide a systematic literature review (SLR) on the scope, measurement, and impact of competition on banking stability. PRISMA technique was used to undertake a meta-analysis of scientific articles. After applying all of the criteria, a total of 42 relevant studies were discovered. Previous research has examined the relationship between banking stability and competition in a variety of countries around the world, and has produced two opposing viewpoints, namely competition fragility and competition stability. The first perspective gets more support. When it comes to the measurement instrument, most studies use the Lerner index to quantify the intensity of competition. It is also discovered that the GMM (Generalized Approach of Moment) approach is widely used. Future research can examine each indicator's strengths and weaknesses further so that it can be used to gauge banking competition in accordance with the banking systems examined in each nation, yielding reliable results. Keywords:    competition, stability, banking